Recent Advances in Chirally-Coupled Core Fibers - Yuan, Mingheng; Sui, Yuan; Bai, Zhenao; Fan, Zhongwei (Frontiers in Physics, 2022)
To meet the needs of high-power fiber lasers, a new fiber structure called chirally coupled core (CCC) fiber has attracted the attention of researchers all over the world. CCC fiber consists of two cores, one of which is a central core distributed along the axial direction, and the other is a side core that is offset from the central axis and spirally distributed around the central core. Meanwhile, CCC fibers are helical-translation symmetric. The unique structure results in advantages of robust single-mode performance, mode-distortion-free splicing and compact coiling of CCC fiber. Based on a brief description of the theory about CCC fiber, this article focuses on the research progress and application prospect of CCC fiber.